Corpus Analysis of Spanish L2 Exam-Based Writing: Lexical Analysis and Indications of Translingualism - Rio Alfinda; Dwiyanto Djoko Pranowo; Agus Widyantoro (International Journal of Pedagogy and Teacher Education, 2025)
This study examines the corpus analysis of lexical richness and the influence of translingualism among high school students, focusing on exam-based argumentative texts in a supervised setting. Lexical richness is a measure used to evaluate written texts. In assessing students' writings, there is an indication of translingualism, or translanguaging, a phenomenon where language switching occurs due to the influence of another language. The study analyzes 21 texts from Spanish students, categorized into three groups, using lexical variation and sophistication measures, classified under lexical richness and translingualism influence. The research evaluates these criteria by applying AntWordProfiler and Microsoft Excel. The results indicate that differences in lexical diversity/variation between the groups are insignificant. In the analysis of lexical sophistication, it is observed that the use of the Academic Word List (AWL) and the General Service List of the first 1000 words is higher among level 2 students than level 3 students. The study also identifies translingualism in students’ texts, influenced by English-Spanish vocabulary similarities. This phenomenon reveals that many misspelled English words are derived from Spanish. Overall, the study provides insights into vocabulary levels, the impact of translingualism, and writing enhancement among high school students.